2015
DOI: 10.1021/acs.molpharmaceut.5b00342
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic Reduction/pH/Temperature Multistimuli-Responsive Nanoparticles for Targeted and Controlled Antitumor Drug Delivery

Abstract: Multistimuli-responsive polymeric nanoparticles with core-shell architecture were prepared by coating superparamagnetic Fe3O4 nanoparticle cores with reduction/pH dual-responsive poly(methacrylic acid) (PMAA) as shells and thermal-responsive poly(N-isopropylacrylamide) (PNIPAM) as a "gatekeeper" on the surface via two-stage distillation precipitation polymerization. The Fe3O4@PMAA nanoparticles were synthesized using N,N-bis(acryloyl)cystamine (BACy) as cross-linker which would be easily biodegradable in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 51 publications
(88 reference statements)
0
22
0
1
Order By: Relevance
“…In a more acidic condition (pH 5.0) shown in Figure 5B, there was a fast DOX release in the initial time and it then reached a plateau as time went on. The DOX cumulative release percentage improved to 48.6% in the initial 3 h and then reached 81.1% within 110 h. Under this acidic condition, the higher cumulative release was due to the electrostatic interaction between the DOX and micelles decreasing [37]. Moreover, the dissolubility of DOX in mildly acidic solution was relative higher than that in neutral media and the deionization of carboxylic acid groups in MAA units resulted in the shrinkage of the micelles' structure to squeeze the entrapped DOX released from polymer micelles [38].…”
Section: Ph-and Gsh-driven In Vitro Dox Release Behaviormentioning
confidence: 88%
“…In a more acidic condition (pH 5.0) shown in Figure 5B, there was a fast DOX release in the initial time and it then reached a plateau as time went on. The DOX cumulative release percentage improved to 48.6% in the initial 3 h and then reached 81.1% within 110 h. Under this acidic condition, the higher cumulative release was due to the electrostatic interaction between the DOX and micelles decreasing [37]. Moreover, the dissolubility of DOX in mildly acidic solution was relative higher than that in neutral media and the deionization of carboxylic acid groups in MAA units resulted in the shrinkage of the micelles' structure to squeeze the entrapped DOX released from polymer micelles [38].…”
Section: Ph-and Gsh-driven In Vitro Dox Release Behaviormentioning
confidence: 88%
“…The magnetic properties of the synthesized nanoparticles can be applied in magnetic resonance imaging (MRI) [17]. Moreover, they can be used as DDS for antibiotics [59], anticancer drugs [60], neurotransmitters [61]. Furthermore, the presence of modifiable functional groups facilitates the attachment of different therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…24,27 The high saturation magnetization (M s ) is observed at 11.2 emu g À1 (corresponding to 0.217 emu for 20 mg mass of the sample) which indicates the presence of magnetite (Fe 3 O 4 ). 15,24,28…”
Section: Thermal and Magnetic Behaviormentioning
confidence: 99%
“…There are several controlled release studies reported for DOX in the literature 1,2,4,7,11,14,17 using GO, 4,20 carbon dots, CNT and supermagnetic nanoparticles such as Fe 3 O 4 . 4,[13][14][15]21 The release of DOX from GO, CNT and carbon dots are preferred due to its higher drug loading capacity (77-90%), and the larger surface area available in the layered materials. 17,18 Xue et al studied the subcellular delivery of doxorubicin from pH-responsive alginate nanogel.…”
Section: Introductionmentioning
confidence: 99%